2014
DOI: 10.1186/1471-2296-15-44
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming the barriers to the diagnosis and management of chronic fatigue syndrome/ME in primary care: a meta synthesis of qualitative studies

Abstract: BackgroundThe NICE guideline for Chronic Fatigue Syndrome/Myalgic Encephalomyelitis (CFS/ME) emphasises the need for an early diagnosis in primary care with management tailored to patient needs. However, GPs can be reluctant to make a diagnosis and are unsure how to manage people with the condition.MethodsA meta synthesis of published qualitative studies was conducted, producing a multi-perspective description of barriers to the diagnosis and management of CFS/ME, and the ways that some health professionals ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 39 publications
0
50
0
1
Order By: Relevance
“…The strain of disparate health beliefs on doctor-ME patient relationships has previously been described (Bayliss et al, 2014). When doctors attribute MUPS conditions to mental and social causes, patients often perceive it as psychologising and trivialising their symptoms (Anderson et al, 2012; Åsbring & Närvänen, 2004; Rosendal et al, 2013; Schoofs et al, 2004).…”
Section: Discussionmentioning
confidence: 88%
“…The strain of disparate health beliefs on doctor-ME patient relationships has previously been described (Bayliss et al, 2014). When doctors attribute MUPS conditions to mental and social causes, patients often perceive it as psychologising and trivialising their symptoms (Anderson et al, 2012; Åsbring & Närvänen, 2004; Rosendal et al, 2013; Schoofs et al, 2004).…”
Section: Discussionmentioning
confidence: 88%
“…Dissatisfaction with medical encounters is a recurrent finding throughout research into patients experiences of conditions where there is no obvious physical cause and research in conditions with medical uncertainty describe that HPs find consultations similarly difficult to manage . Some research found HPs attributed negative personality characteristics to their patients rather than acknowledging their own lack of knowledge causing conflict and difficulties in the doctor‐patient relationships, and lack of coherence and difficulties in the doctor‐patient relationship may reflect the lack of confidence of HPs in diagnosing and managing this condition, which has been found in other research …”
Section: Discussionmentioning
confidence: 91%
“…14 Some research found HPs attributed negative personality characteristics to their patients rather than acknowledging their own lack of knowledge causing conflict and difficulties in the doctor-patient relationships, 40 and lack of coherence and difficulties in the doctor-patient relationship may reflect the lack of confidence of HPs in diagnosing and managing this condition, which has been found in other research. 36,48,50…”
Section: Theme 4: Impact On Mental Health and Role For Psychology-"mentioning
confidence: 99%
“…Thus, a model to understand the illness phases and fluctuations in functional level is needed. General practitioners (GPs) may feel uncomfortable in making the diagnosis or defining the condition [37], and health professionals have a limited understanding of it [38]. Because appropriate advice and support from health care professionals may vary during the illness trajectory, there is a need to understand how the disabilities are experienced in different phases and how the severity of different disabilities is experienced by the persons affected.…”
Section: Introductionmentioning
confidence: 99%